Milk kefir: composition, microbial cultures, biological activities, and related products - Prado, Maria R.; Blandón, Lina Marcela; Vandenberghe, Luciana P. S.; Rodrigues, Cristine; Castro, Guillermo R.; Thomaz-Soccol, Vanete; Soccol, Carlos R. (Frontiers in Microbiology, 2015)
In recent years, there has been a strong focus on beneficial foods with probiotic microorganisms and functional organic substances. In this context, there is an increasing interest in the commercial use of kefir, since it can be marketed as a natural beverage that has health promoting bacteria. There are numerous commercially available kefir based-products. Kefir may act as a matrix in the effective delivery of probiotic microorganisms in different types of products. Also, the presence of kefir’s exopolysaccharides, known as kefiran, which has biological activity, certainly adds value to products. Kefiran can also be used separately in other food products and as a coating film for various food and pharmaceutical products. This article aims to update the information about kefir and its microbiological composition, biological activity of the kefir’s microflora and the importance of kefiran as a beneficial health substance.